Occupational Stress among Women Employees with Technical and Without Technical Skills: Impact of Technical Skills on Occupational Stress Among Women Employees (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Stress is worldwide scenario, seen across all areas of life and among all age groups. It’s an major areas of research. Stress effects an individual physical and emotionally. Due to changes in society many women take up working as a career .The present study try’s to investigate the role of having technical skill in performing their job and its effect of occupational stress. The present study aims to assess occupational stress among women employees with technical and without technical skills a study was conducted on 300 women employees working in Bengaluru city. Their occupational stress was assessed by administering occupational stress index developed by A. K. Srivastava and A. P. Singh. A Suitable stastical technique was used to analyzes the obtained results.